Seminar on Global Classroom (GC) 2023 Bringing the World into the Classroom - Amy Zulaikha, Mohd Ali; Jamilah Bebe, Mohamad (UMPSA, 2023)
PEKAN, 4 July 2023 - The Centre for Modern Languages (CML), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has been making significant strides in the realm of global education with its Global Classroom initiative, as demonstrated through the monthly appreciation posters created by the Centre of Instructional Resources and E-Learning (CIREL).